Early development of a novel scale to measure adaptation in people diagnosed with inflammatory bowel disease - the A-inflammatory bowel disease. Issue 1 (15th July 2022) - Matini, Lawrence; Ogden, Jane
Objective: To undergo the preliminary development of a new measure of patient adaptation to Inflammatory Bowel Disease (IBD): A-IBD. Design: Based on a prior conceptualisation of adaptation, a 40-item scale was generated and completed by 304 people diagnosed with IBD. Main outcome measures: Psychometric analysis of the measure. Association with the Brief Illness Perception Questionnaire (Brief IPQ) and the Inflammatory Bowel Disease Questionnaire (IBDQ). Results: The 18-item scale consisted of four subscales (patient identity, person identity, acceptance, expectations). Weak to moderate correlations were found between subscales of the A-IBD and the Brief IPQ and IBDQ. Conclusion: The A-IBD shows potential for assessing adaptation. Further analysis could confirm its usefulness.